Synergistic apoptosis in head and neck squamous cell carcinoma cells by co‐inhibition of insulin‐like growth factor‐1 receptor signaling and compensatory signaling pathways. Issue 12 (6th April 2015) - Axelrod, Mark J.; Mendez, Rolando E.; Khalil, Ashraf; Leimgruber, Stephanie S.; Sharlow, Elizabeth R.; Capaldo, Brian; Conaway, Mark; Gioeli, Daniel G.; Weber, Michael J.; Jameson, Mark J.
ABSTRACT: Background: In head and neck squamous cell carcinoma (HNSCC), resistance to single‐agent targeted therapy may be overcome by co‐targeting of compensatory signaling pathways. Methods: A targeted drug screen with 120 combinations was used on 9 HNSCC cell lines. Results: Multiple novel drug combinations demonstrated synergistic growth inhibition. Combining the insulin‐like growth factor‐1 receptor (IGF‐1R) inhibitor, BMS754807, with either the human epidermal growth factor receptor (HER)‐family inhibitor, BMS599626, or the Src‐family kinase inhibitor, dasatinib, resulted in substantial synergy and growth inhibition. Depending on the cell line, these combinations induced synergistic or additive apoptosis; when synergistic apoptosis was observed, AKT phosphorylation was inhibited to a greater extent than either drug alone. Conversely, when additive apoptosis occurred, AKT phosphorylation was not reduced by the drug combination. Conclusion: Combined IGF‐1R/HER family and IGF‐1R/Src family inhibition may have therapeutic potential in HNSCC. AKT may be a node of convergence between IGF‐1R signaling and pathways that compensate for IGF‐1R inhibition. © 2015 Wiley Periodicals, Inc. Head Neck 37: 1722–1732, 2015